The Online Advertising Tax as the Foundation of a Public Service Internet - Fuchs, Christian

Nationalism 2.0. The Making of Brexit on Social Media - Fuchs, Christian

Karl Marx @ 200. Debating Capitalism & Perspectives for the Future of Radical Theory - Fuchs, Christian; Monticelli, Lara (tripleC: Communication, Capitalism & Critique)

Karl Marx @ 200: Towards a Marxian Theory of Communication - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Racism, Nationalism and Right-Wing Extremism Online: The Austrian Presidential Election 2016 on Facebook - Fuchs, Christian (Critical Theory and Authoritarian Populism)

What would Marx have said about Facebook and Cambridge Analytica? - Fuchs, Christian (Monthly Review Online, November 28, 2018)

What Would Marx Have Said About Facebook and Cambridge Analytica? - Fuchs, Christian (openDemocracy)

Universal Alienation, Formal and Real Subsumption of Society Under Capital, Ongoing Primitive Accumulation by Dispossession: Reflections on the Marx@200-Contributions by David Harvey and Michael Hardt/Toni Negri - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Repeating Marx: Introduction to the Special Issue “Karl Marx @ 200: Debating Capitalism & Perspectives for the Future of Radical Theory“ - Fuchs, Christian; Monticelli, Lara (tripleC: Communication, Capitalism & Critique)

Reflections on Sven-Eric Liedman’s Marx-Biography “A World to Win: The Life and Works of Karl Marx” - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Postface: Horst Holzer’s “Communication & Society: A Critical Political Economy Perspective“ - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Karl Marx & Rosa Luxemburg: Postface to Rosa Luxemburg’s Article “Karl Marx” - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Marx’s Centenary (1918) in the Light of the Media and Socialist Thought - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

How Corbyn’s Plan to Tax Google and Facebook Could Create A Public Service Internet - Fuchs, Christian (Huffington Post UK)

Written Evidence Submitted to the House of Lords-Communications Select Committee Inquiry “The Internet: To Regulate Or Not To Regulate?“, Published on May 9, 2018 - Fuchs, Christian

Porous Aluminum Oxide and Magnesium Oxide Films Using Organic Hydrogels as Structure Matrices - Chen, Zimei; Kuckling, Dirk; Tiemann, Michael (Nanomaterials)
We describe the synthesis of mesoporous Al2O3 and MgO layers on silicon wafer substrates by using poly(dimethylacrylamide) hydrogels as porogenic matrices. Hydrogel films are prepared by spreading the polymer through spin-coating, followed by photo-cross-linking and anchoring to the substrate surface. The metal oxides are obtained by swelling the hydrogels in the respective metal nitrate solutions and subsequent thermal conversion. Combustion of the hydrogel results in mesoporous metal oxide layers with thicknesses in the μm range and high specific surface areas up to 558 m2∙g−1. Materials are characterized by SEM, FIB ablation, EDX, and Kr physisorption porosimetry.

Hydrogels as Porogens for Nanoporous Inorganic Materials - Weinberger, Christian; Kuckling, Dirk; Tiemann, Michael (Gels)
Organic polymer-hydrogels are known to be capable of directing the nucleation and growth of inorganic materials, such as silica, metal oxides, apatite or metal chalcogenides. This approach can be exploited in the synthesis of materials that exhibit defined nanoporosity. When the organic polymer-based hydrogel is incorporated in the inorganic product, a composite is formed from which the organic component may be selectively removed, yielding nanopores in the inorganic product. Such porogenic impact resembles the concept of using soft or hard templates for porous materials. This micro-review provides a survey of select examples from the literature.

Einleitung: Die „jüngere Queerfeminist*in“ spricht. - Degeling, Jasmin; Deuber-Mankowsky, Astrid; Horn, Sarah; Shnayien, Mary (onlinejournal kultur & geschlecht)

Teoria e análise do trabalho digital: Das cadeias globais de valor aos modos de produção (Translated by Rodrigo Moreno Marques) - Fuchs, Christian (Trabalho & Educação)

Media Theory, Public Relevance and the Propaganda Model - Klaehn, Jeffery; Broudy, Daniel; Fuchs, Christian; Godler, Yigal; Zollmann, Florian; Chomsky, Noam; Pedro-Carañana, Joan; Mills, Tom; Boyd-Barrett, Oliver (Media Theory)

The Rise of Authoritarian Capitalism - Fuchs, Christian (Global Dialogue)

Why There Are Certain Parallels Between Joachim C. Fest’s Hitler-Biography and Michael Wolff’s Trump-Book - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

How Can Creating A Public Service Internet Challenge the Power of Google and Facebook? - Fuchs, Christian (The Drum)

Digitale Demokratie und Öffentlich-Rechtliche Medien [Digital Democracy and Public Service Media] - Fuchs, Christian (ORF Public Value Studie 2017/2018: Der Auftrag: Demokratie [ORF Public Value Study 2017/2018: The Mission: Democracy])

Industry 4.0: The Digital German Ideology - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

netCommons Political and Ethical Guidelines for an Alternative Internet. EU Horizon 2020 Project netCommons, Deliverable 4.4 (December 2018) - Fuchs, Christian

Die Abschaffung der Netzneutralität, oder: Die Kolonialisierung digitaler Räume - Rolf, Carolin; Shnayien, Mary (onlinejournal kultur & geschlecht)
Mit der Abschaffung der Netzneutralität in den USA im Dezember 2017 wurden in der internationalen Debatte Interessenskonflikte bezüglich der Regulierung des Internets für eine breitere Öffentlichkeit sichtbar. Der Artikel gibt eine Einführung in die technischen Grundprinzipien des Internets und die Voraussetzungen von Netzneutralität und diskutiert auf dieser Basis verschiedene aktivistische Positionen anhand der Beispiele von queerem Aktivismus in den USA und dem Kampf für ein netzneutrales Internet in Indien, der unter dem Begriff des digitalen Kolonialismus geführt wird.

Populärkultur - Adelmann, Ralf (Von Automatismen bis Zersetzung. Wörterbuch-Projekt des Graduiertenkollegs Automatismen)

Methoden empirischer Bildungsforschung im Kontext Frühkindliche Bildung und Entwicklung

Weiblichkeit – Ansätze zur Theoretisierung.
Der Band will dazu beitragen, differenziertere Ansätze zum theoretischen Verständnis von Weiblichkeitskonstruktionen zu entwickeln. Die Beiträge diskutieren unterschiedliche Aspekte wie Diskurse über Weiblichkeit, Auseinandersetzungen mit analytischen Fassungen einer ‚hegemonialen Weiblichkeit‘, Brückenschläge zu leibtheoretischen Überlegungen, zum Spannungsfeld von Weiblichkeit und Mütterlichkeit sowie zur Rolle entsprechender Zuschreibungen in pädagogischen oder beraterischen Settings. Wie lässt sich über Weiblichkeit sprechen, wenn zugleich bezweifelt wird, ob es sie überhaupt gibt? Wenn die konstruktivistische Perspektive auf Geschlecht dieses als kontingente Zuschreibung definiert? Wenn in jedem Sprechen die Gefahr besteht, ungewollt vereindeutigende Zuschreibungen vorzunehmen und sie damit zu reifizieren? Das Anliegen des hier vorgelegten Bandes folgte vor allem aus der Feststellung, dass derzeit sehr viel über Männlichkeit und Väterlichkeit geforscht wird, aktuelle Arbeiten zum relationalen und begrifflichen Pendant Weiblichkeit jedoch weitgehend fehlen – und damit eine wesentliche Voraussetzung dafür, theoriegeleitete Überlegungen zu Geschlecht und Geschlechtervorstellungen weiter entwickeln zu können. Die in diesem Band versammelten Beiträge erhellen je unterschiedlich einzelne Aspekte dieser komplexen Zusammenhänge und tragen dazu bei, die diffus erscheinende Leerstelle im Wissen über aktuelle Weiblichkeitskonstruktionen sowohl mit feldspezifischen empiriebezogenen Analysen zu füllen als auch zu veranschaulichen, warum es aus einer Perspektive der Geschlechterforschung, die sich ihrerseits kritisch mit ihrer eigenen Wissensproduktion und den damit einhergehenden eigenen Entwürfen und Ausschlüssen auseinandersetzt, so schwierig scheint, ‚Weiblichkeit‘ als relevanten Forschungsgegenstand zu fassen. Die Beiträge diskutieren unterschiedliche Aspekte wie Diskurse über Weiblichkeit, Auseinandersetzungen mit analytischen Fassungen einer ‚hegemonialen Weiblichkeit‘, Brückenschläge zu leibtheoretischen Überlegungen, zum Spannungsfeld von Weiblichkeit und Mütterlichkeit sowie zur Rolle entsprechender Zuschreibungen in pädagogischen oder beraterischen Settings. Mit Beiträgen von Meike Baader, Astrid Messerschmidt, Arzu Cicek, Carrie Paechter, Melanie Kubandt, Maya Halatcheva-Trapp, Bastian Lasse, Frauke Grenz, Anna Orlikowski

Local intersections of Lagrangian manifolds correspond to catastrophe theory - Offen, Christian (arXiv:1811.10165)
Two smooth map germs are right-equivalent if and only if they generate two Lagrangian submanifolds in a cotangent bundle which have the same contact with the zero-section. In this paper we provide a reverse direction to this classical result of Golubitsky and Guillemin. Two Lagrangian submanifolds of a symplectic manifold have the same contact with a third Lagrangian submanifold if and only if the intersection problems correspond to stably right equivalent map germs. We, therefore, obtain a correspondence between local Lagrangian intersection problems and catastrophe theory while the classical version only captures tangential intersections. The correspondence is defined independently of any Lagrangian fibration of the ambient symplectic manifold, in contrast to other classical results. Moreover, we provide an extension of the correspondence to families of local Lagrangian intersection problems. This gives rise to a framework which allows a natural transportation of the notions of catastrophe theory such as stability, unfolding and (uni-)versality to the geometric setting such that we obtain a classification of families of local Lagrangian intersection problems. An application is the classification of Lagrangian boundary value problems for symplectic maps.

Hamiltonian boundary value problems, conformal symplectic symmetries, and conjugate loci - McLachlan, Robert I; Offen, Christian (New Zealand Journal of Mathematics)
In this paper we continue our study of bifurcations of solutions of boundary-value problems for symplectic maps arising as Hamiltonian diffeomorphisms. These have been shown to be connected to catastrophe theory via generating functions and ordinary and reversal phase space symmetries have been considered. Here we present a convenient, coordinate free framework to analyse separated Lagrangian boundary value problems which include classical Dirichlet, Neumann and Robin boundary value problems. The framework is then used to prove the existence of obstructions arising from conformal symplectic symmetries on the bifurcation behaviour of solutions to Hamiltonian boundary value problems. Under non-degeneracy conditions, a group action by conformal symplectic symmetries has the effect that the flow map cannot degenerate in a direction which is tangential to the action. This imposes restrictions on which singularities can occur in boundary value problems. Our results generalise classical results about conjugate loci on Riemannian manifolds to a large class of Hamiltonian boundary value problems with, for example, scaling symmetries.
Keywords: Hamiltonian boundary value problems; singularities; conformal symplectic geometry; catastrophe theory; conjugate loci

Front-End Processing for the CHiME-5 Dinner Party Scenario - Boeddeker, Christoph; Heitkaemper, Jens; Schmalenstroeer, Joerg; Drude, Lukas; Heymann, Jahn; Haeb-Umbach, Reinhold (Proc. CHiME 2018 Workshop on Speech Processing in Everyday Environments, Hyderabad, India)
This contribution presents a speech enhancement system for the CHiME-5 Dinner Party Scenario. The front-end employs multi-channel linear time-variant filtering and achieves its gains without the use of a neural network. We present an adaptation of blind source separation techniques to the CHiME-5 database which we call Guided Source Separation (GSS). Using the baseline acoustic and language model, the combination of Weighted Prediction Error based dereverberation, guided source separation, and beamforming reduces the WER by 10:54% (relative) for the single array track and by 21:12% (relative) on the multiple array track.

Discrimination of Stationary from Moving Targets with Recurrent Neural Networks in Automotive Radar - Grimm, Christopher; Breddermann, Tobias; Farhoud, Ridha; Fei, Tai; Warsitz, Ernst; Haeb-Umbach, Reinhold (International Conference on Microwaves for Intelligent Mobility (ICMIM) 2018)
In this paper, we present a neural network based classification algorithm for the discrimination of moving from stationary targets in the sight of an automotive radar sensor. Compared to existing algorithms, the proposed algorithm can take into account multiple local radar targets instead of performing classification inference on each target individually resulting in superior discrimination accuracy, especially suitable for non rigid objects, like pedestrians, which in general have a wide velocity spread when multiple targets are detected.

Full Bayesian Hidden Markov Model Variational Autoencoder for Acoustic Unit Discovery - Glarner, Thomas; Hanebrink, Patrick; Ebbers, Janek; Haeb-Umbach, Reinhold (INTERSPEECH 2018, Hyderabad, India)
The invention of the Variational Autoencoder enables the application of Neural Networks to a wide range of tasks in unsupervised learning, including the field of Acoustic Unit Discovery (AUD). The recently proposed Hidden Markov Model Variational Autoencoder (HMMVAE) allows a joint training of a neural network based feature extractor and a structured prior for the latent space given by a Hidden Markov Model. It has been shown that the HMMVAE significantly outperforms pure GMM-HMM based systems on the AUD task. However, the HMMVAE cannot autonomously infer the number of acoustic units and thus relies on the GMM-HMM system for initialization. This paper introduces the Bayesian Hidden Markov Model Variational Autoencoder (BHMMVAE) which solves these issues by embedding the HMMVAE in a Bayesian framework with a Dirichlet Process Prior for the distribution of the acoustic units, and diagonal or full-covariance Gaussians as emission distributions. Experiments on TIMIT and Xitsonga show that the BHMMVAE is able to autonomously infer a reasonable number of acoustic units, can be initialized without supervision by a GMM-HMM system, achieves computationally efficient stochastic variational inference by using natural gradient descent, and, additionally, improves the AUD performance over the HMMVAE.

Der ‚Verlust der natürlichen Selbstverständlichkeit‘ in Phänomenologie und Psychopathologie - Philippi, Martina (InterCultural Philosophy)
Die Habilitationsschrift des Psychopathologen Wolfgang Blankenburg thematisiert die ‚Grundstörung‘ in symptomarmen Schizophrenien, die das Korrelat zur ‚natürlichen Selbstverständlichkeit‘ des gesunden Lebensvollzugs darstellt. Für die Phänomenologie Husserlscher Provenienz ist diese von besonderer methodischer und inhaltlicher Bedeutung. Mein Beitrag zeigt auf, wie die Problematik der Selbstverständlichkeit als Kernthema von Husserls Phänomenologie gelesen werden kann, vor welche Herausforderungen sie sowohl die Phänomenologie als auch die Psychopathologie und Psychotherapie stellt und wie sich beide Ansätze wechselseitig befruchten können, d. h. wie durch eine Zusammenschau der Disziplinen die Phänomenologie mit anthropologisch-lebensweltlichen und die Psychopathologie und Psychotherapie um existenzielle Aspekten bereichert werden kann.
Keywords: Alltag; Wolfgang Blankenburg; Erkenntnistheorie; Edmund Husserl; Phänomenologie; Psychopathologie; Selbstverständlichkeit; Weltvertrauen

In depth Raman analysis of the ferroelectrics KTiOPO4 and LiNbO3: role of domain boundaries and defect - Rüsing, Michael
In the context of ferroelectrics spatially resolved Raman spectroscopy is a powerful tool to investigate stoichiometry, defects or the ferroelectric properties, as well as to visualize domain structures or waveguides. Using Raman spectroscopy for investigations requires a throughout understanding of the spectra and underlying mechanisms. For example, in the context of the common nonlinear materials, lithium niobate and potassium titanyl phosphate, no comprehensive understanding of the Raman spectra of the bulk materials is available, while the underlying mechanism of the domain wall contrast in Raman spectroscopy is not well understood. In this work, questions like these have been addressed in terms of systematic experimental investigations in close cooperation with density functional theory. In particular, it was possible to present a complete assignment of all phonons in the lithium niobate system, which serves as the basis for the understanding of the domain wall spectrum. Here, the domain wall spectrum can be explained with regard to microscopic structural effects, such as strains and electric fields, as well as a macroscopic change of selections rules. Both mechanisms are likewise present in the domain wall spectrum, while being present at different length scales. In the context of potassium titanyl phosphate the first throughout Raman investigations of domain structure, waveguides and periodically poled waveguides are presented. In the context of Rb-exchanged waveguides the change in stoichiometry, but also effects of strain are detected. Here, the Raman analysis provides a method to evaluate these effects.

Wortschatzerweiterung in autonomen Erwerbskontexten - Kilsbach, Sebastian

Efficient Sampling Rate Offset Compensation - An Overlap-Save Based Approach - Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (26th European Signal Processing Conference (EUSIPCO 2018))
Distributed sensor data acquisition usually encompasses data sampling by the individual devices, where each of them has its own oscillator driving the local sampling process, resulting in slightly different sampling rates at the individual sensor nodes. Nevertheless, for certain downstream signal processing tasks it is important to compensate even for small sampling rate offsets. Aligning the sampling rates of oscillators which differ only by a few parts-per-million, is, however, challenging and quite different from traditional multirate signal processing tasks. In this paper we propose to transfer a precise but computationally demanding time domain approach, inspired by the Nyquist-Shannon sampling theorem, to an efficient frequency domain implementation. To this end a buffer control is employed which compensates for sampling offsets which are multiples of the sampling period, while a digital filter, realized by the wellknown Overlap-Save method, handles the fractional part of the sampling phase offset. With experiments on artificially misaligned data we investigate the parametrization, the efficiency, and the induced distortions of the proposed resampling method. It is shown that a favorable compromise between residual distortion and computational complexity is achieved, compared to other sampling rate offset compensation techniques.

The RWTH/UPB System Combination for the CHiME 2018 Workshop - Kitza, Markus; Michel, Wilfried; Boeddeker, Christoph; Heitkaemper, Jens; Menne, Tobias; Schlüter, Ralf; Ney, Hermann; Schmalenstroeer, Joerg; Drude, Lukas; Heymann, Jahn; Haeb-Umbach, Reinhold (Proc. CHiME 2018 Workshop on Speech Processing in Everyday Environments, Hyderabad, India)
This paper describes the systems for the single-array track and the multiple-array track of the 5th CHiME Challenge. The final system is a combination of multiple systems, using Confusion Network Combination (CNC). The different systems presented here are utilizing different front-ends and training sets for a Bidirectional Long Short-Term Memory (BLSTM) Acoustic Model (AM). The front-end was replaced by enhancements provided by Paderborn University [1]. The back-end has been implemented using RASR [2] and RETURNN [3]. Additionally, a system combination including the hypothesis word graphs from the system of the submission [1] has been performed, which results in the final best system.

Benchmarking Neural Network Architectures for Acoustic Sensor Networks - Ebbers, Janek; Heitkaemper, Jens; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (ITG 2018, Oldenburg, Germany)
Due to their distributed nature wireless acoustic sensor networks offer great potential for improved signal acquisition, processing and classification for applications such as monitoring and surveillance, home automation, or hands-free telecommunication. To reduce the communication demand with a central server and to raise the privacy level it is desirable to perform processing at node level. The limited processing and memory capabilities on a sensor node, however, stand in contrast to the compute and memory intensive deep learning algorithms used in modern speech and audio processing. In this work, we perform benchmarking of commonly used convolutional and recurrent neural network architectures on a Raspberry Pi based acoustic sensor node. We show that it is possible to run medium-sized neural network topologies used for speech enhancement and speech recognition in real time. For acoustic event recognition, where predictions in a lower temporal resolution are sufficient, it is even possible to run current state-of-the-art deep convolutional models with a real-time-factor of 0:11.

Insights into the Interplay of Sampling Rate Offsets and MVDR Beamforming - Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (ITG 2018, Oldenburg, Germany)
It has been experimentally verified that sampling rate offsets (SROs) between the input channels of an acoustic beamformer have a detrimental effect on the achievable SNR gains. In this paper we derive an analytic model to study the impact of SRO on the estimation of the spatial noise covariance matrix used in MVDR beamforming. It is shown that a perfect compensation of the SRO is impossible if the noise covariance matrix is estimated by time averaging, even if the SRO is perfectly known. The SRO should therefore be compensated for prior to beamformer coefficient estimation. We present a novel scheme where SRO compensation and beamforming closely interact, saving some computational effort compared to separate SRO adjustment followed by acoustic beamforming.

New Quick And Easy Publication - Will be edited by LibreCat team - Taschl-Erber, Andrea (Quick And Easy Journal Title)

Blue Blood in the Red? Nobles on the Antwerp annuity market (1490-1493) - Huybrechts, Yves; Buylaert, Frederik (EDAD MEDIA: Revista de Historia)

Astronomie in der Lehrerausbildung - Hohmann, Sascha; Quast, Martin (PhyDid B)

Reziprozität zwischen Lehrenden und Studierenden als Kern der Kompetenzorientierung – eine didaktisch-praktische Anwendung - Hoyer, Isabelle; Corves, Annette; Nyquist, Elin; Reis, Oliver (Neues Handbuch Hochschullehre)

Reziprozität zwischen Lehrenden und Studierenden als Kern der Kompetenzorientierung – eine Grundsatzklärung - Hoyer, Isabelle; Corves, Annette; Nyquist, Elin; Reis, Oliver (Neues Handbuch Hochschullehre)

Phänomenologie und Philosophiedidaktik - Albus, Vanessa; Philipp, Thomas (Zeitschrift für Didaktik der Philosophie und Ethik)

Konzeption von fachmathematischen Schnittstellenmodulen für Lehramtsstudierende am Beispiel ausgewählter Themen der höheren Analysis. - Hoffmann, Max

Chor-Individuen. Anmerkungen zur ‚realistisch‘ bewegten Chordramaturgie in Les Huguenots und Le Prophète - Münzmay, Andreas (Bild und Bewegung im Musiktheater. Interdisziplinäre Studien im Umfeld der Grand Opéra / Image and Movement in Music Theatre. Interdisciplinary Studies around Grand Opéra)
Wie versetzen Eugène Scribe und Giacomo Meyerbeer den Chor auf der Opernbühne in Bewegung – in innere Bewegung, und ebenso in äußere –, so dass diese Bewegung spontan und ›realistisch‹ erscheint? Ausgehend von einigen allgemeinen Thesen zur Musikdramaturgie Scribe’scher Grands opéras will die vorliegende Lektüre von Libretti, Partituren und livrets de mise en scène einige Schlaglichter auf prominente Momente der Gruppen- und Chordramaturgie in Les Huguenots und Le Prophète werfen. Stärker als bislang üblich soll dabei auch die zentrale Rolle der Librettistik herausgestellt werden, die insbesondere im Bereich der Exposition und dramaturgischen Führung der Nebenrollen entscheidende Voraussetzungen schafft. Zudem soll die gängige Lesart, wonach Meyerbeers Chordramaturgie im Kern eine Dramaturgie der ›Massen‹ sei, differenziert und in bestimmter Hinsicht auch relativiert werden. Die Ensemble- und Chordramaturgien in Les Huguenots und Le Prophéte können gleichermaßen als Beispiele der eingangs umrissenen Scribe’schen dramaturgischen Grundtechnik gelesen werden, die darauf beruht, die Verständnisgrundlagen der Stücke vollständig und lückenlos im Inneren der Stücke selbst zu vermitteln. (Es gibt nichts, was man schon vorher über Hugenotten oder Anabaptisten wissen müsste, um die Intrigen von Les Huguenots bzw. Le Prophète in allen Details zu verstehen.) Die Verfahren einer ›realistischen‹ Chordramaturgie mithilfe einer Vielzahl librettistisch bereitgestellter Nebenrollen, die als ›Chor-Individuen‹ selbst die ›Massen‹-Chöre gleichsam als maximierte Ensembles konfigurieren und dadurch von Innen heraus plausibilisieren, haben genau in diesem Zusammenhang in beiden Werken eine tragende Funktion: Gerade diese beiden Werke setzen eine Dynamik der ›Massen‹ nicht etwa einfach als Zeitphänomene und allgemeine Erfahrung voraus, sondern lassen im Gegenteil mit großer (musik)dramaturgischer Präzision das Wirken von ›Massen‹ als Folge des Handelns von lauter Individuen erscheinen.

Der FID Musikwissenschaft (Musiconn) in Lehre und Forschung. Kommentar aus Nutzer-Perspektive - Münzmay, Andreas (Zeitschrift für Bibliothekswesen und Bibliographie (ZfBB))
Keywords: Library and Information Sciences

Virtualitäten der Opéra comique und XML-Kode als ‚Teleskop‘ - Münzmay, Andreas (Symposiumsbericht ‚Virtualitäten des Barock. Deleuze und musikalische Analyse‘)
Die französische Opéra comique in ihrer Umbruchphase nach 1750 kann im Sinne Gilles Deleuzes als idealtypisch ›barock‹ begriffen werden. Die vermeintlich simplen musikalischen Oberflächen, auf die Analyse in den unzähligen Opéras comiques des 18. Jahrhunderts immer dann trifft, wenn Melodiezitate im Spiel sind, sind dabei integraler Teil eines komplexen wissenskulturellen Systems. Können die Begriffe der »Falte« und der »Virtualität« eine poststrukturalistisch inspirierte Analyse befördern, die an das Hypertextualitätskonzept, wie es Gérard Genette 1982 mit Palimpsestes: La littérature au second degré so griffig systematisiert hat, anschließt, aber auch darüber hinaus geht? Um diese Frage soll es im ersten Teil des vorliegenden Versuchs gehen. Im zweiten Teil soll überlegt werden, auf welche spezifische Weise XML-Codierung (als Kernverfahren digitaler Edition) und analytische Erkenntnismöglichkeiten interagieren. Anlass und Materialbasis für einen solchen Ausblick auf digitale Editionsmethoden soll die 2016 erschienene digitale Edition des Werks Annette et Lubin von Justine Favart sein, die in etwa sechsjähriger Arbeit im Frankfurter Akademienprojekt OPERA – Spektrum des europäischen Musiktheaters. Historisch-kritische Hybridausgaben erarbeitet werden konnte.

Lesen und Schreiben im digitalen Dickicht. Musikwissenschaft, Digital Humanities und die hybride Musikbibliothek - Münzmay, Andreas (Bibliothek: Forschung und Praxis)
Digitalisierung generiert ‚hybride‘ Objekte, die zwar als digitale Datei lesbar und manipulierbar sind, das zugrundeliegende kulturhistorische Objekt jedoch weiterhin ‚enthalten‘. Eine Bibliothek, die Objekte aus ihren Beständen digitalisiert, begründet also eigentlich keine sog. digitale Bibliothek, sondern eine hybride Bibliothek. Im Falle musikalischer Überlieferung ist die Sachlage aufgrund der medienhistorischen Komplexität musikalischer Artefakte besonders unübersichtlich. Verschärft wird die heutige Situation noch durch die Erzeugnisse der Digital Humanities, die keineswegs bloß ‚Informationen‘ sind, sondern ihrerseits komplexe und in der Regel hybride Textgebilde, die häufig komplette digitalisierte Re-Publikationen von Kulturobjekten einbinden, die digital ‚beschriftet‘ und vernetzt werden. Das digitale ‚Dickicht‘ erfordert einen gleichsam genetischen und relationalen Katalog, in dem die konkreten kulturhistorischen Objekte in ihren konkreten Sammlungskontexten – also als Unikate – Ankerfunktion haben. Der Essay geht zurück auf einen Vortrag bei der AIBM-Jahrestagung, Symposium der AG Musikabteilungen an wissenschaftlichen Bibliotheken, Detmold, 8. September 2016.

Boundary Values of Eigenfunctions on Riemannian Symmetric Spaces - Hilgert, Joachim; Hansen, S.; Parthasarathy, A.

,Queer‘ aufs Spiel gesetzt: Über Beißreflexe, queere Bewegungsgeschichte und gegenwärtige Affektkulturen. (Best Publication Award Gender&Medien 2019) - Degeling, Jasmin; Horn, Sarah (onlinejournal kultur&geschlecht 21)

Rezension zu: Yost, Jeffrey R.: Making IT Work. A History of the Computer Services Industry. Cambridge 2017 - Schmitt, Martin (H-Soz-Kult)

Rezension zu „Vaterunser. Das Gebet Jesu neu gelesen“ (2018) von Papst Franziskus mit Marco Pozza - Breckner, Anne (Blog des Instituts für Evangelische Theologie an der Universität Paderborn)

Einfach frei Schnauze. Religiöse Parodien der Reformationszeit - Breckner, Anne (TheoMag. Tà katoptrizómena. Das Magazin für Kunst – Kultur – Theologie – Ästhetik)

Vernetzte Bankenwelt. Computerisierung in der Kreditwirtschaft der Bundesrepublik und der DDR - Schmitt, Martin (Wege in die digitale Gesellschaft. Computernutzung in der Bundesrepublik 1955-1990)

Über Mehrsprachigkeit und Migration nachdenken und sprechen. Migrationspädagogische Perspektiven auf den Einsatz sog. Migrationsliteratur im Deutschunterricht - Büttner, Denise

Dokumentation der Auftaktveranstaltung zur 2. Förderphase von ProDaZ - Büttner, Denise

Numerical analysis of partial differential equations on and of evolving surfaces - Kovács, Balázs

Zwischen studentischer Diversität und fachlicher Homogenisierung. Die wertbezogene Hochschuldidaktik als Vermittlerin im Habituskonflikt - Reis, Oliver (Hochschuldidaktik forscht zu Vielfalt und Offenheit Profilbildung und Wertefragen in der Hochschulentwicklung I)

Понять, как они тикают [Verstehen, wie sie ticken]. Interview on CLIL conducted by Ирина Долженко [Irina Dolzhenko] on behalf of sib.fm - Dolzhenko, Irina; Rumlich, Dominik

Radar backscattering from a large-grain cometary coma: numerical simulation - Dogra, Shraddha; Grynko, Yevgen; Zubko, Evgenij; Förstner, Jens (Astronomy & Astrophysics)
We numerically simulate the circular polarization ratio of the radar signal backscattered from a large-grain cometary coma and compare the simulation results with the radar measurements for seven comets. We apply the discrete dipole approximation method and a model of random irregular particles. Our results confirm water ice composition of the cm-sized chunks detected by the NASA Deep Impact space probe in the vicinity of the nucleus of Comet 103P/Hartley 2. The index of the power-law size distribution in this case can be constrained to the range n ≈ 3.3–4.3. For the other considered comets the circular polarization ratio can be reproduced with variations of the power index between 2 and 5.
Keywords: tet_topic_scattering

Hybrid coupled-mode modeling in 3D: perturbed and coupled channels, and waveguide crossings - Hammer, Manfred; Alhaddad, Samer; Förstner, Jens (Journal of the Optical Society of America B)
The 3D implementation of a hybrid analytical/numerical variant of the coupled-mode theory is discussed. Eigenmodes of the constituting dielectric channels are computed numerically. The frequency-domain coupled-mode models then combine these into fully vectorial approximations for the optical electromagnetic fields of the composite structure. Following a discretization of amplitude functions by 1D finite elements, pro- cedures from the realm of finite-element numerics are applied to establish systems of linear equations for the then- discrete modal amplitudes. Examples substantiate the functioning of the technique and allow for some numerical assessment. The full 3D simulations are highly efficient in memory consumption, moderately demanding in com- putational time, and, in regimes of low radiative losses, sufficiently accurate for practical design. Our results include the perturbation of guided modes by changes of the refractive indices, the interaction of waves in parallel, horizontally or vertically coupled straight waveguides, and a series of crossings of potentially overlapping channels with fairly arbitrary relative positions and orientations.
Keywords: tet_topic_waveguide; tet_topic_numerics

Direction-tunable enhanced emission from a subwavelength metallic double-nanoslit structure - Song, Xiaohong; Wang, Nini; Yan, Ming; Lin, Cheng; Förstner, Jens; Yang, Weifeng (Optics Express)
Controlling light emission out of subwavelength nanoslit/aperture structures is of great important for highly integrated photonic circuits. Here we propose a new method to achieve direction-tunable emission based on a compact metallic microcavity with double nanoslit. Our method combines the principles of Young’s interference and surface plasmon polaritons interference. We show that the direction of the far-field beam can be controlled over a wide range of angles by manipulating the frequency and relative phase of light arriving at the two slits, which holds promise for applications in the ultracompact optoelectronic devices.
Keywords: tet_topic_plasmonics

Subtleties in Security Definitions for Predicate Encryption with Public Index - Blömer, Johannes; Liske, Gennadij (Proceedings of the International Conference of Mathematical Aspects of Computer and Information Sciences (MACIS))

Searchable Encryption with Access Control - Löken, Nils (Proceedings of the 12th International Conference on Availability, Reliability and Security - ARES '17)

Attribute-Based Encryption as a Service for Access Control in Large-Scale Organizations - Blömer, Johannes; Günther, Peter; Krummel, Volker; Löken, Nils (Foundations and Practice of Security)

2016 Global MNC Tax Complexity Survey - Executive Summary - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren

What are the Drivers of Tax Complexity for Multinational Corporations? Evidence from 108 Countries - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren
All over the world, firms and governments are increasingly concerned about the rise in tax complexity. To manage it and develop effective simplification measures, detailed information on the current drivers of complexity is required. However, research on this topic is scarce. This is surprising as the latest developments—for example, triggered by the BEPS project—give rise to the conjecture that complexity drivers may have changed, thus questioning the findings of prior studies. In this paper, we shed light on this issue and provide a global picture of the current drivers of tax complexity that multinational corporations face based on a survey of 221 highly experienced tax practitioners from 108 countries. Our results show that prior complexity drivers of the tax code are still relevant, with details and changes of tax regulations being the two most influential complexity drivers. We also find evidence for new relevant complexity drivers emerging from different areas of the tax framework, such as inconsistent decisions among tax officers (tax audits) or retroactively applied tax law amendments (tax enactment). Based on the responses of the practitioners, we develop a concept of tax complexity that distinguishes two pillars, tax code and tax framework complexity, and illustrates the various aspects that should be considered when assessing the complexity of a country’s tax system.
Keywords: Complexity Drivers; International Comparison; Survey; Tax Complexity; Tax Practitioners

Sinnkonstruktion beim Erkunden von Mustern und Strukturen - Schumacher, Jan (Beiträge zum Mathematikunterricht 2017)

Algorithms for Max-Min Share Fair Allocation of Indivisible Chores - Aziz, Haris; Rauchecker, Gerhard; Schryen, Guido; Walsh, Toby (Thirty-First AAAI Conference on Artificial Intelligence (AAAI-17))
We consider Max-min Share (MmS) fair allocations of indivisible chores (items with negative utilities). We show that allocation of chores and classical allocation of goods (items with positive utilities) have some fundamental connections but also differences which prevent a straightforward application of algorithms for goods in the chores setting and viceversa. We prove that an MmS allocation does not need to exist for chores and computing an MmS allocation - if it exists - is strongly NP-hard. In view of these non-existence and complexity results, we present a polynomial-time 2-approximation algorithm for MmS fairness for chores. We then introduce a new fairness concept called optimal MmS that represents the best possible allocation in terms of MmS that is guaranteed to exist. We use connections to parallel machine scheduling to give (1) a polynomial-time approximation scheme for computing an optimal MmS allocation when the number of agents is fixed and (2) an effective and efficient heuristic with an ex-post worst-case analysis.

Specification, Composition, and Placement of Network Services with Flexible Structures - Dräxler, Sevil; Karl, Holger (International Journal of Network Management)
Network function virtualization and software-defined networking allow services consisting of virtual network functions to be designed and implemented with great flexibility by facilitating automatic deployments, migrations, and reconfigurations for services and their components. For extended flexibility, we go beyond seeing services as a fixed chain of functions. We define the service structure in a flexible way that enables changing the order of functions in case the functionality of the service is not influenced by this, and propose a YANG data model for expressing this flexibility. Flexible structures allow the network orchestration system to choose the optimal composition of service components that for example gives the best results for placement of services in the network. When number of flexible services and number of components in each service increase, combinatorial explosion limits the practical use of this flexibility. In this paper, we describe a selection heuristic that gives a Pareto set of the possible compositions of a service as well as possible combinations of different services, with respect to different optimization objectives. Moreover, we present a heuristic algorithm for placement of a combination of services, which aims at placing service components along shortest paths that have enough capacity for accommodating the services. By applying these solutions, we show that allowing flexibility in the service structure is feasible.

Service-oriented Cost Allocation for Business Intelligence and Analytics: Who pays for BI&A? - Grytz, Raphael; Krohn-Grimberghe, Artus (Proceedings of the 50th Hawaii International Conference on System Sciences (2017))
Quantifying and designing the cost pool generated by Business Intelligence and Analytics (BI&A) would improve cost transparency and invoicing processes, allowing a fairer, more exact allocation of costs to service consumers. Yet there is still no method for determining BI&A costs to provide a base for allocation purposes. While literature describes several methods for BI&A cost estimation on an ROI or resource-consumption level, none of these methods considers an overall approach for BI&A. To tackle this problem, we propose a service-oriented cost allocation model which calculates BI&A applications based on defined services, enabling a cost transfer to service consumers. This new approach specifies steps towards deriving a usable pricing scheme for an entire BI&A service portfolio – both for allocation purposes as well as improving cost evaluation of BI&A projects. Moreover, it prevents BI&A departments from being considered as the sole cost driver, increasing customer understanding and cost awareness.

SONATA: Service programming and orchestration for virtualized software networks - Dräxler, Sevil; Karl, Holger; Peuster, Manuel; Razzaghi Kouchaksaraei, Hadi; Bredel, Michael; Lessmann, Johannes; Soenen, Thomas; Tavernier, Wouter; Mendel-Brin, Sharon; Xilouris, George (2017 IEEE International Conference on Communications Workshops (ICC Workshops))
In conventional large-scale networks, creation and management of network services are costly and complex tasks that often consume a lot of resources, including time and manpower. Network softwarization and network function virtualization have been introduced to tackle these problems, aiming at decreasing costs and complexity of implementing new services, maintaining the implemented services, and managing available resources in service provisioning platforms and underlying infrastructures. To experience the full potential of these approaches, innovative development support tools and service provisioning environments are needed. To answer these needs, we introduce the architecture of the open-source SONATA system, a service programming, orchestration, and management framework. We present a development toolchain for virtualized network services, fully integrated with a service platform and orchestration system. We introduce the modular and flexible architecture of our system and discuss its main components and features, such as function- and service-specific managers that allow fine-grained service management, slicing support to facilitate multi-tenancy, recursiveness for improved scalability, and full-featured DevOps support.

A flexible multi-pop infrastructure emulator for carrier-grade MANO systems - Peuster, Manuel; Dräxler, Sevil; Razzaghi Kouchaksaraei, Hadi; van Rossem, Steven; Tavernier, Wouter; Karl, Holger (IEEE Conference on Network Softwarization, NetSoft 2017, Bologna, Italy, July 3-7, 2017)
Developing a virtualized network service does not only involve the implementation and configuration of the network functions it is composed of but also its integration and test with management solutions that will control the service in its production environment. These integration tasks require testbeds that offer the needed network function virtualization infrastructure~(NFVI), like OpenStack, introducing a lot of management and maintenance overheads. Such testbed setups become even more complicated when the multi point-of-presence~(PoP) case, with multiple infrastructure installations, is considered. In this demo, we showcase an emulation platform that executes containerized network services in user-defined multi-PoP topologies. The platform does not only allow network service developers to locally test their services but also to connect real-world management and orchestration solutions to the emulated PoPs. During our interactive demonstration we focus on the integration between the emulated infrastructure and state-of-the-art orchestration solutions like SONATA or OSM.

Joint Optimization of Scaling and Placement of Virtual Network Services - Dräxler, Sevil; Karl, Holger; Mann, Zoltan Adam (Proceedings of the 17th IEEE/ACM International Symposium on Cluster, Cloud and Grid Computing (CCGrid 2017))
Management of complex network services requires flexible and efficient service provisioning as well as optimized handling of continuous changes in the workload of the service.To adapt to changes in the demand, service components need to be replicated (scaling) and allocated to physical resources (placement) dynamically. In this paper, we propose a fullyautomated approach to the joint optimization problem of scaling and placement, enabling quick reaction to changes. We formalize the problem, analyze its complexity, and develop two algorithms to solve it. Extensive empirical results show the applicability andeffectiveness of the proposed approach.

Profile Your Chains, Not Functions. Automated Network Service Profiling in DevOps Environments - Peuster, Manuel; Karl, Holger (IEEE Conference on Network Function Virtualisation and Software Defined Networks (NFV-SDN))
Benchmarking and profiling virtual network functions (VNFs) generates input knowledge for resource management decisions taken by management and orchestration systems. Such VNFs are usually not executed in isolation but are often deployed as part of a service function chain (SFC) that connects single functions into complex structures. To manage such chains, isolated performance profiles of single functions have to be combined to get insights into the overall behavior of an SFC. This becomes particularly challenging in highly agile DevOps environments in which profiling processes need to be fully automated and detailed insights about a chain's internal structures are not always available. In this paper, we introduce a fully automatable, flexible, and platform-agnostic profiling system that allows to profile entire SFCs at once. This obviates manual modeling procedures to combine profiling results from single VNFs to reflect SFC performance. We use a case study with different SFC configurations to show that it is hard to model the resulting SFC performance based on single-VNF measurements and that performance interactions between real, non-trivial functions that are deployed in a chain exist.

"A variational formulation for fuzzy analysis in continuum mechanics" - Mahnken, Rolf (Mathematics and Mechanics of complex systems)
In order to improve the credibility of modern simulation tools, uncertainties of different kinds have to be considered. This work is focused on epistemic uncertainties in the framework of continuum mechanics, which are taken into account by fuzzy analysis. The underlying min-max optimization problem of the extension principle is approximated by α-discretization, resulting in a separation of minimum and maximum problems. To become more universal, so-called quantities of interest are employed, which allow a general formulation for the target problem of interest. In this way, the relation to parameter identification problems based on least-squares functions is highlighted. The solutions of the related optimization problems with simple constraints are obtained with a gradient-based scheme, which is derived from a sensitvity analysis for the target problem by means of a variational formulation. Two numerical examples for the fuzzy analysis of material parameters are concerned with a necking problem at large strain elastoplasticity and a perforated strip at large strain hyperelasticity to demonstrate the versatility of the proposed variational formulation.
Keywords: fuzzy analysis; α-level optimization; quantities of interest; optimization with simple constraints; large strain elasticity; large strain elastoplasticity

Exploring the Scientific Impact of Information Systems Design Science Research: A Scientometric Study - Wagner, Gerit; Prester, Julian; Schryen, Guido (38th International Conference on Information Systems)
Design science is a fundamental research stream that contends its position in the information systems discipline. While ongoing debates address the relative importance of design science contributions in the information systems community, insights into the scientific impact of design science research (DSR) are missing and this lack of understanding arguably poses challenges to an informed discourse. To identify the most influential papers and those factors that explain their scientific impact, this paper presents an exploratory study of the scientific impact of DSR papers published in the AIS Senior Scholars' Basket of Journals. We uncover the current DSR landscape by taking stock of influential papers and theories and develop a model to explain the scientific impact of DSR papers. Our findings show that scientific impact is significantly explained by theorization and novelty. We discuss how the implications of our work can be projected on the overarching discourse on DSR.

Literature Reviews in IS Research: What Can Be Learnt from the Past and Other Fields? - Schryen, Guido; Benlian, Alexander; Rowe, Frantz; Shirley, Gregor; Larsen, Kai; Petter, Stacie; Paré, Guy; Wagner, Gerit; Haag, Steffi; Yasasin, Emrah (Communications of the AIS)
Literature reviews (LRs) are recognized for their increasing impact in the information systems literature. Methodologists have drawn attention to the question of how we can leverage the value of LRs to preserve and generate knowledge. The panelists who participated in the discussion of ?Standalone Literature Reviews in IS Research: What Can Be Learnt from the Past and Other Fields?? at ICIS 2016 in Dublin acknowledged this significant issue and debated a) what the IS field can learn from other fields and where IS-specific challenges occur, b) how the IS field should move forward to foster the genre of LRs, and c) what best practices are to train doctoral IS students in publishing LRs. This article reports the key takeaways of this panel discussion. Guidance for IS scholars is provided on how to conduct LRs that contribute to the cumulative knowledge development within and across the IS field to best prepare the next generation of IS scholars.
Keywords: Literature Review; Review Methodology; Research Methodology; Doctoral Training

A configuration-based recommender system for supporting e-commerce decisions - Scholz, Michael; Dorner, Verena; Schryen, Guido; Benlian, Alexander (European Journal of Operational Research)
Multi-attribute value theory (MAVT)-based recommender systems have been proposed for dealing with issues of existing recommender systems, such as the cold-start problem and changing preferences. However, as we argue in this paper, existing MAVT-based methods for measuring attribute importance weights do not fit the shopping tasks for which recommender systems are typically used. These methods assume well-trained decision makers who are willing to invest time and cognitive effort, and who are familiar with the attributes describing the available alternatives and the ranges of these attribute levels. Yet, recommender systems are most often used by consumers who are usually not familiar with the available attributes and ranges and who wish to save time and effort. Against this background, we develop a new method, based on a product configuration process, which is tailored to the characteristics of these particular decision makers. We empirically compare our method to SWING, ranking-based conjoint analysis and TRADEOFF in a between-subjects laboratory experiment with 153 participants. Results indicate that our proposed method performs better than TRADEOFF and CONJOINT and at least as well as SWING in terms of recommendation accuracy, better than SWING and TRADEOFF and at least as well as CONJOINT in terms of cognitive load, and that participants were faster with our method than with any other method. We conclude that our method is a promising option to help support consumers' decision processes in e-commerce shopping tasks.
Keywords: E-Commerce; Recommender System; Attribute Weights; Configuration System; Decision Support

WSDM Cup 2017: Vandalism Detection and Triple Scoring - Heindorf, Stefan; Potthast, Martin; Bast, Hannah; Buchhold, Björn; Haussmann, Elmar (WSDM)

Directional Emission from Dielectric Leaky-Wave Nanoantennas - Peter, Manuel; Hildebrandt, Andre; Schlickriede, Christian; Gharib, Kimia; Zentgraf, Thomas; Förstner, Jens; Linden, Stefan (Nano Letters)
Keywords: tet_topic_opticalantenna

Exploiting structure in multiobjective optimization and optimal control - Peitz, Sebastian
Multiobjective optimization plays an increasingly important role in modern applications, where several criteria are often of equal importance. The task in multiobjective optimization and multiobjective optimal control is therefore to compute the set of optimal compromises (the Pareto set) between the conflicting objectives. Since – in contrast to the solution of a single objective optimization problem – the Pareto set generally consists of an infinite number of solutions, the computational effort can quickly become challenging. This is even more the case when many problems have to be solved, when the number of objectives is high, or when the objectives are costly to evaluate. Consequently, this thesis is devoted to the identification and exploitation of structure both in the Pareto set and the dynamics of the underlying model as well as to the development of efficient algorithms for solving problems with additional parameters, with a high number of objectives or with PDE-constraints. These three challenges are addressed in three respective parts. In the first part, predictor-corrector methods are extended to entire Pareto sets. When certain smoothness assumptions are satisfied, then the set of parameter dependent Pareto sets possesses additional structure, i.e. it is a manifold. The tangent space can be approximated numerically which yields a direction for the predictor step. In the corrector step, the predicted set converges to the Pareto set at a new parameter value. The resulting algorithm is applied to an example from autonomous driving. In the second part, the hierarchical structure of Pareto sets is investigated. When considering a subset of the objectives, the resulting solution is a subset of the Pareto set of the original problem. Under additional smoothness assumptions, the respective subsets are located on the boundary of the Pareto set of the full problem. This way, the “skeleton” of a Pareto set can be computed and due to the exponential increase in computing time with the number of objectives, the computations of these subsets are significantly faster which is demonstrated using an example from industrial laundries. In the third part, PDE-constrained multiobjective optimal control problems are addressed by reduced order modeling methods. Reduced order models exploit the structure in the system dynamics, for example by describing the dynamics of only the most energetic modes. The model reduction introduces an error in both the function values and their gradients, which has to be taken into account in the development of algorithms. Both scalarization and set-oriented approaches are coupled with reduced order modeling. Convergence results are presented and the numerical benefit is investigated. The algorithms are applied to semi-linear heat flow problems as well as to the Navier-Stokes equations.

Matching Strategies of Heterogeneous Agents under Incomplete Information in a University Clearinghouse - Hoyer, Britta; Stroh-Maraun, Nadja
In actual school choice applications the theoretical underpinnings of the Boston School Choice Mechanism (BM) (complete information and rationality of the agents) are often not given. We analyze the actual behavior of agents in such a matching mechanism, using data from the matching mechanism currently used in a clearinghouse at a faculty of Business Administration and Economics at a German university, where a variant of the BM is used, and supplement this data with data generated in a survey among students who participated in the clearinghouse. We find that under the current mechanism over 70% of students act strategically. Controlling for students' limited information, we find that they do act rationally in their decision to act strategically. While students thus seem to react to the incentives to act strategically under the BM, they do not seem to be able to use this to their own advantage. However, those students acting in line with their beliefs manage a significantly better personal outcome than those who do not. We also run simulations by using a variant of the deferred acceptance algorithm, adapted to our situation, to show that the use of a different algorithm may be to the students' advantage.

Cooperative static analysis of Android applications - Pauck, Felix

Towards a Lean Approach for Gamifying Education - John, Thomas; Feldotto, Matthias; Hemsen, Paul; Klingsieck, Katrin; Kundisch, Dennis; Langendorf, Mike (Proceedings of the 25th European Conference on Information Systems (ECIS))
Many university students struggle with motivational problems, and gamification has the potential to address these problems. However, using gamification currently is rather tedious and time-consuming for instructors because current approaches to gamification require instructors to engage in the time-consuming preparation of course contents (e.g., for quizzes or mini-games). In reply to this issue, we propose a “lean” approach to gamification, which relies on gamifying learning activities rather than learning contents. The learning activities that are gamified in the lean approach can typically be drawn from existing course syllabi (e.g., attend certain lectures, hand in assignments, read book chapters and articles). Hence, compared to existing approaches, lean gamification substantially lowers the time requirements posed on instructors for gamifying a given course. Drawing on research on limited attention and the present bias, we provide the theoretical foundation for the lean gamification approach. In addition, we present a mobile application that implements lean gamification and outline a mixed-methods study that is currently under way for evaluating whether lean gamification does indeed have the potential to increase students’ motivation. We thereby hope to allow more students and instructors to benefit from the advantages of gamification.

A Study on Transfer Learning for Acoustic Event Detection in a Real Life Scenario - Arora, Prerna; Haeb-Umbach, Reinhold (IEEE 19th International Workshop on Multimedia Signal Processing (MMSP))
In this work, we address the limited availability of large annotated databases for real-life audio event detection by utilizing the concept of transfer learning. This technique aims to transfer knowledge from a source domain to a target domain, even if source and target have different feature distributions and label sets. We hypothesize that all acoustic events share the same inventory of basic acoustic building blocks and differ only in the temporal order of these acoustic units. We then construct a deep neural network with convolutional layers for extracting the acoustic units and a recurrent layer for capturing the temporal order. Under the above hypothesis, transfer learning from a source to a target domain with a different acoustic event inventory is realized by transferring the convolutional layers from the source to the target domain. The recurrent layer is, however, learnt directly from the target domain. Experiments on the transfer from a synthetic source database to the reallife target database of DCASE 2016 demonstrate that transfer learning leads to improved detection performance on average. However, the successful transfer to detect events which are very different from what was seen in the source domain, could not be verified.

On the Computation of Complex-valued Gradients with Application to Statistically Optimum Beamforming - Boeddeker, Christoph; Hanebrink, Patrick; Drude, Lukas; Heymann, Jahn; Haeb-Umbach, Reinhold
This report describes the computation of gradients by algorithmic differentiation for statistically optimum beamforming operations. Especially the derivation of complex-valued functions is a key component of this approach. Therefore the real-valued algorithmic differentiation is extended via the complex-valued chain rule. In addition to the basic mathematic operations the derivative of the eigenvalue problem with complex-valued eigenvectors is one of the key results of this report. The potential of this approach is shown with experimental results on the CHiME-3 challenge database. There, the beamforming task is used as a front-end for an ASR system. With the developed derivatives a joint optimization of a speech enhancement and speech recognition system w.r.t. the recognition optimization criterion is possible.

Optimizing Neural-Network Supported Acoustic Beamforming by Algorithmic Differentiation - Boeddeker, Christoph; Hanebrink, Patrick; Drude, Lukas; Heymann, Jahn; Haeb-Umbach, Reinhold (Proc. IEEE Intl. Conf. on Acoustics, Speech and Signal Processing (ICASSP))
In this paper we show how a neural network for spectral mask estimation for an acoustic beamformer can be optimized by algorithmic differentiation. Using the beamformer output SNR as the objective function to maximize, the gradient is propagated through the beamformer all the way to the neural network which provides the clean speech and noise masks from which the beamformer coefficients are estimated by eigenvalue decomposition. A key theoretical result is the derivative of an eigenvalue problem involving complex-valued eigenvectors. Experimental results on the CHiME-3 challenge database demonstrate the effectiveness of the approach. The tools developed in this paper are a key component for an end-to-end optimization of speech enhancement and speech recognition.

A Generalized Log-Spectral Amplitude Estimator for Single-Channel Speech Enhancement - Chinaev, Alleksej; Haeb-Umbach, Reinhold (Proc. IEEE Intl. Conf. on Acoustics, Speech and Signal Processing (ICASSP))
The benefits of both a logarithmic spectral amplitude (LSA) estimation and a modeling in a generalized spectral domain (where short-time amplitudes are raised to a generalized power exponent, not restricted to magnitude or power spectrum) are combined in this contribution to achieve a better tradeoff between speech quality and noise suppression in single-channel speech enhancement. A novel gain function is derived to enhance the logarithmic generalized spectral amplitudes of noisy speech. Experiments on the CHiME-3 dataset show that it outperforms the famous minimum mean squared error (MMSE) LSA gain function of Ephraim and Malah in terms of noise suppression by 1.4 dB, while the good speech quality of the MMSE-LSA estimator is maintained.

Tight integration of spatial and spectral features for BSS with Deep Clustering embeddings - Drude, Lukas; Haeb-Umbach, Reinhold (INTERSPEECH 2017, Stockholm, Schweden)
Recent advances in discriminatively trained mask estimation networks to extract a single source utilizing beamforming techniques demonstrate, that the integration of statistical models and deep neural networks (DNNs) are a promising approach for robust automatic speech recognition (ASR) applications. In this contribution we demonstrate how discriminatively trained embeddings on spectral features can be tightly integrated into statistical model-based source separation to separate and transcribe overlapping speech. Good generalization to unseen spatial configurations is achieved by estimating a statistical model at test time, while still leveraging discriminative training of deep clustering embeddings on a separate training set. We formulate an expectation maximization (EM) algorithm which jointly estimates a model for deep clustering embeddings and complex-valued spatial observations in the short time Fourier transform (STFT) domain at test time. Extensive simulations confirm, that the integrated model outperforms (a) a deep clustering model with a subsequent beamforming step and (b) an EM-based model with a beamforming step alone in terms of signal to distortion ratio (SDR) and perceptually motivated metric (PESQ) gains. ASR results on a reverberated dataset further show, that the aforementioned gains translate to reduced word error rates (WERs) even in reverberant environments.

Leveraging Text Data for Word Segmentation for Underresourced Languages - Glarner, Thomas; Boenninghoff, Benedikt; Walter, Oliver; Haeb-Umbach, Reinhold (INTERSPEECH 2017, Stockholm, Schweden)
In this contribution we show how to exploit text data to support word discovery from audio input in an underresourced target language. Given audio, of which a certain amount is transcribed at the word level, and additional unrelated text data, the approach is able to learn a probabilistic mapping from acoustic units to characters and utilize it to segment the audio data into words without the need of a pronunciation dictionary. This is achieved by three components: an unsupervised acoustic unit discovery system, a supervisedly trained acoustic unit-to-grapheme converter, and a word discovery system, which is initialized with a language model trained on the text data. Experiments for multiple setups show that the initialization of the language model with text data improves the word segementation performance by a large margin.

Automatic Machine Learning: Hierachical Planning Versus Evolutionary Optimization - Wever, Marcel Dominik; Mohr, Felix; Hüllermeier, Eyke (27th Workshop Computational Intelligence)
These days, there is a strong rise in the needs for machine learning applications, requiring an automation of machine learning engineering which is referred to as AutoML. In AutoML the selection, composition and parametrization of machine learning algorithms is automated and tailored to a specific problem, resulting in a machine learning pipeline. Current approaches reduce the AutoML problem to optimization of hyperparameters. Based on recursive task networks, in this paper we present one approach from the field of automated planning and one evolutionary optimization approach. Instead of simply parametrizing a given pipeline, this allows for structure optimization of machine learning pipelines, as well. We evaluate the two approaches in an extensive evaluation, finding both approaches to have their strengths in different areas. Moreover, the two approaches outperform the state-of-the-art tool Auto-WEKA in many settings.

BEAMNET: End-to-End Training of a Beamformer-Supported Multi-Channel ASR System - Heymann, Jahn; Drude, Lukas; Boeddeker, Christoph; Hanebrink, Patrick; Haeb-Umbach, Reinhold (Proc. IEEE Intl. Conf. on Acoustics, Speech and Signal Processing (ICASSP))
This paper presents an end-to-end training approach for a beamformer-supported multi-channel ASR system. A neural network which estimates masks for a statistically optimum beamformer is jointly trained with a network for acoustic modeling. To update its parameters, we propagate the gradients from the acoustic model all the way through feature extraction and the complex valued beamforming operation. Besides avoiding a mismatch between the front-end and the back-end, this approach also eliminates the need for stereo data, i.e., the parallel availability of clean and noisy versions of the signals. Instead, it can be trained with real noisy multichannel data only. Also, relying on the signal statistics for beamforming, the approach makes no assumptions on the configuration of the microphone array. We further observe a performance gain through joint training in terms of word error rate in an evaluation of the system on the CHiME 4 dataset.

A Generic Neural Acoustic Beamforming Architecture for Robust Multi-Channel Speech Processing - Heymann, Jahn; Drude, Lukas; Haeb-Umbach, Reinhold (Computer Speech and Language)
Acoustic beamforming can greatly improve the performance of Automatic Speech Recognition (ASR) and speech enhancement systems when multiple channels are available. We recently proposed a way to support the model-based Generalized Eigenvalue beamforming operation with a powerful neural network for spectral mask estimation. The enhancement system has a number of desirable properties. In particular, neither assumptions need to be made about the nature of the acoustic transfer function (e.g., being anechonic), nor does the array configuration need to be known. While the system has been originally developed to enhance speech in noisy environments, we show in this article that it is also effective in suppressing reverberation, thus leading to a generic trainable multi-channel speech enhancement system for robust speech processing. To support this claim, we consider two distinct datasets: The CHiME 3 challenge, which features challenging real-world noise distortions, and the Reverb challenge, which focuses on distortions caused by reverberation. We evaluate the system both with respect to a speech enhancement and a recognition task. For the first task we propose a new way to cope with the distortions introduced by the Generalized Eigenvalue beamformer by renormalizing the target energy for each frequency bin, and measure its effectiveness in terms of the PESQ score. For the latter we feed the enhanced signal to a strong DNN back-end and achieve state-of-the-art ASR results on both datasets. We further experiment with different network architectures for spectral mask estimation: One small feed-forward network with only one hidden layer, one Convolutional Neural Network and one bi-directional Long Short-Term Memory network, showing that even a small network is capable of delivering significant performance improvements.

Active Learning of User Requirement Specifications in Dynamic Software Service Markets - Wever, Marcel Dominik